Povest' o nastoiashchem cheloveke - Stolpner, Alexander (Soviet Union : Mosfilm, 1948)
The film is based on the life story of Alexey Meres'ev, a fighter pilot during World War II. One day he is shot down by Nazis, and both of his legs have to be amputated at the knee. Alexey manages to overcome his disability: he learns not only to walk on his artificial limbs, but to dance and to fly again.
Keywords: Fiction films